Biolasers: Microsphere Solid‐State Biolasers (Advanced Optical Materials 8/2017). Issue 8 (April 2017) - Ta, Van Duong; Caixeiro, Soraya; Fernandes, Francisco M.; Sapienza, Riccardo
Abstract : Microsphere solid‐state biolasers made of biomaterials, which include bovine serum albumin, pectin, and cellulose, are demonstrated in article number 1601022 by Van Duong Ta and co‐workers. The lasers are compatible with cell growth and division, as in the cover image where a 30 μm biolaser is incubated with HeLa cells.